A conformational analysis for leucine-enkephalin using activity and binding data of synthetic analogues. - Beddell, C R (1977)
1. Leucine-enkephalin and some analogues were assayed for activity in vitro on the mouse vas deferens and for binding to opiate receptors from rat brain. 2. The experimental data were analysed in terms of the stringency for glycine, a D-amino acid or an L-amino acid at each position in the peptide. 3. The observed configurational specificity was compared with the stringency that would be predicted to occur if enkephalin adopted certain hydrogen-bonded conformations at the receptor. 4. A small subset of the conformations examined was found to be compatible with the experimental data.